Intravenous immunoglobulin for interstitial lung diseases of anti-melanoma differentiation-associated gene 5-positive dermatomyositis. (23rd December 2021) - Wang, Li-Mei; Yang, Qi-Hua; Zhang, Lei; Liu, Sheng-Yun; Zhang, Pan-Pan; Zhang, Xin; Liu, Xiao-Jun; Han, Li-Shuai; Li, Tian-Fang
Abstract: Objective: Rapidly progressive interstitial lung disease (RP-ILD) in DM patients positive for anti-melanoma differentiation-associated gene 5 (anti-MDA5) autoantibody (MDA5-DM) often have a poor prognosis, frequently fatal. As there is a scarcity of data regarding the effect of intravenous immunoglobulin (IVIG) on RP-ILD in MDA5-DM patients (MDA5-RPILD), we conducted this study to determine the efficacy of a IVIG add-on initial treatment. Methods: Patients with newly-onset MDA5-RPILD from September 2018 to June 2020 were retrospectively reviewed for 6 months in the First Affiliated Hospital of Zhengzhou University. They were divided into two groups: IVIG and non-IVIG groups. The major measurement of treatment outcome was the difference in the mortality in 3-month and 6-month between two group patients. Other relevant indicators were also recorded, including the incidence of infection, the dosages of GCs, the remission rate and the variables in laboratory data. Results: The IVIG group ( n = 31) showed significantly lower 6-month mortality rate than the non-IVIG group ( n = 17) (22.6% vs 52.9%; P =0.033). The IVIG group patients had a higher remission rate at 3 months (71.0% vs 41.2%; P =0.044). Gradual reduction was observed in the first 3 months with regard to the titre of anti-MDA5 autoantibody, the serum level of ferritin and the ground glass opacification GGO scores. Conclusion: IVIG adjunct therapy is a very effective first-line treatment for patients with MDA5-RPILD. IVIG may increase the survival and remission rate by lowering ferritin concentration, anti-MDA5 titre and GGO score.